Realizing high photovoltaic efficiency with parallel multijunction solar cells based on spectrum-splitting and -concentrating diffractive optical element - 王进泽 黄庆礼 许信 全宝钢 罗建恒 张岩 叶佳声 李冬梅 孟庆波 杨国桢 (Chinese physics B, 2015)
Based on the facts that multijunction solar cells can increase the efficiency and concentration can reduce the cost dramatically, a special design of parallel multijunction solar cells was presented. The design employed a diffractive optical element （DOE） to split and concentrate the sunlight. A rainbow region and a zero-order diffraction region were generated on the output plane where solar cells with corresponding band gaps were placed. An analytical expression of the light intensity distribution on the output plane of the special DOE was deduced, and the limiting photovoltaic efficiency of such parallel multijunction solar ceils was obtained based on Shockley-Queisser＇s theory. An efficiency exceeding the Shockley--Queisser limit （33%） can be expected using multijunction solar cells consisting of separately fabricated subcells. The results provide an important alternative approach to realize high photovoltaic efficiency without the need for expensive epitaxial technology widely used in tandem solar cells, thus stimulating the research and application of high efficiency and low cost solar cells.